Pendampingan Orang Tua dalam Penggunaan Literasi Media Belajar Anak Sekolah Dasar di Sungai Kapas - Tri Wiyoko; Yogi Irdes Saputra; Aprizan Aprizan; Ahmad Ridoh (Warta LPM, 2022)
Parents have an important role in guiding each of their children’s development, especially in choosing children’s learning literacy media during the COVID-19 pandemic. This is so that the time given to study from home can be used as well as possible. This mentoring activity was carried out in Sungai Kapas village. The method applied is service learning which consists of planning, implementation and evaluation. There were 15 participants who took part in this activity. The results of the service evaluation show that parents who realize the importance of accompanying their children in choosing literacy sources are 100%. Then the parents who are ready to accompany their children in completing their learning tasks are 85%. This shows that parental assistance for the use of learning media literacy for elementary school children in Sungai Kapas has a good effect. Parents increase their knowledge and awareness to pay attention to their children when learning. The commitment to provide assistance to children is the key to the success of the role of parents in monitoring children’s learning development during the COVID-19 pandemic by choosing learning literacy media that are appropriate for their age. The success or failure of children in understanding the material assigned by the school during learning from home is strongly influenced by parents.